THE PREDICTING FACTORS OF SUCCESS IN THE INDONESIAN NATIONAL NURSING COMPETENCY TEST - Yakobus Siswadi; Christine L Sommers; Grace Solely Houghty (Universitas Pelita Harapan, 2021)
The implementation of the Indonesian National Nursing Competency Test faces several challenges, especially those associated with low passing rates. Low passing rates are a concern of all nursing schools because they reflect the quality of the institution. The purpose of this study was to determine the factors predicting success on the Indonesia National Nursing Competency Test. The research design was descriptive correlational. Participants in the study were 201 alumni of the Faculty of Nursing at Universitas Pelita Harapan in Indonesia. Statistical tests showed a significant correlation between academic achievement (academic stage GPA, professional stage GPA, English proficiency score, and tryout) and the national competency test, while demographic data showed no significant correlation. Academic achievement plays a significant role in success on the Indonesian National Nursing Competency Test.BAHASA INDONESIA ABSTRACT: Pelaksanaan Uji Kompetensi Nasional Perawat Indonesia menghadapi banyak tantangan terutama berakitan dengan rendahnya tingkat kelulusan. Tingkat kelulusan yang rendah menjadi perhatian dari semua institusi pendidikan keperawatan karena hal ini menjadi potret dari institusi. Tujuan penelitian ini untuk menjelaskan faktor-faktor prediksi keberhasilan dalam Uji Kompetensi Nasional Perawat Indonesia. Design penelitian menggunakan deskripsi korelasi. Partisipan penelitian adalah alumni Fakultas Keperawatan Universitas Pelita Harapan Indonesia sejumlah 201. Uji statistic menunjukan korelasi yang signifikan antara hasil bidang akademik (IPK tahap akademik, IPK tahap profesi, nilai kemampuan bahasa Inggris, dan try out) dengan uji kompetensi test, sedangkan data demografi tidak menunjukan korelasi yang signifikan. Pencapaian bidang akademik memiliki peran signifikan didalam keberhasilan pada Uji Kompetensi Nasional Perawat Indonesia.